Durability Study of Malaysia Rock Mass for Tunnelling Construction - Zarime N.A.; Solemon B.; Omar R.C.; Wahab W.A.; Mohd Taher T.; Roslan R.; Baharuddin I.N.Z.; Abdullah R.A.; Vigneswaran V.; Isa A.A.A. (Springer Science and Business Media Deutschland GmbH, 2024)
The weathering, faults, shear zones, and thrust zones that have formed in igneous and metamorphic rocks in Malaysia make the compressive strengths less than 50MPa. These factors make the development of rock energy tunnels in Malaysia a complex process. Malaysias rapid expansion and population growth have led to the development of numerous infrastructure and amenities, including tunnel projects to facilitate the network system and increase traffic flow. Engineering considerations such as the behavior and strength of rock mass must be considered when planning for the safe and affordable building of tunnels. Tunnel excavation and support systems should be designed accordingly. It is crucial to prevent ground collapse, which could cause the loss of life and property. Hence, the primary aim of this investigation is to evaluate the strength and durability of Malaysian rock masses intended for tunnelling applications through the utilization of Rebound Hammer and slake durability tests. The results of the current study showed that the worse weathering grades for Granite rock and Schist-Phyllite (metamorphic rock) were II and II/III respectively, with all rocks suitable with durability classification of longer span. The results showed that the Schist-Phyllite rock samples also had extremely high durability strengths, while Granite 16 had very high durability strengths. This study also concludes the most suitable place for each rock type's particular mass based on its durability. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.